Delayed Cord Clamping Increased the Need for Phototherapy Treatment in Infants With AB0 Alloimmunization Born by Cesarean Section: A Retrospective Study - Stefano Ghirardello; Beatrice L. Crippa; Valeria Cortesi; Elena Di Francesco; Dario Consonni; Lorenzo Colombo; Monica Fumagalli; Arjan B. te Pas; Fabio Mosca (Frontiers Media S.A., 2018)
Objective: To compare the effect of Delayed Cord Clamping (DCC) to Immediate Cord Clamping (ICC) on phototherapy treatment in a cohort of cesarean-delivered newborns with AB0-alloimmunization.Study Design: In a retrospective cohort study neonates with Gestational Age (GA) ≥ 35 weeks and diagnosed with AB0-alloimmunization before implementation of DCC (ICC group) were compared with neonates born after implementation (DCC group). The primary outcome was the need for phototherapy. Secondary outcomes included hospital stay, readmission rate, need for extra intravenous fluids, maximum bilirubin concentration, and hours of life at bilirubin peak. We used regression models to adjust for weight loss, type of feeding, birth weight, and gestational age.Results: In total 336 neonates were included, of which 192 neonates in the ICC group and 144 in the DCC group. There were no differences in basic characteristics between the two groups except for birth weight (ICC 3193 ± 468 g vs. DCC 3053 ± 446 g, p = 0.01) and GA (ICC 38.2 ± 1 weeks of GA, vs. DCC 37.9 ± 1 weeks of GA; p = 0.01). When adjusted for confounding factors, after implementation of DCC, significantly more infants with AB0 alloimmunization needed phototherapy (22.4% vs. 36.8%, RR 1.61 CI: 1.15-2.28; p = 0.006; Number Needed to Harm 7), needed to stay longer in hospital (20.3% vs. 30.5%, RR 1.53 CI: 1.05-2.23; p = 0.03). The maximum bilirubin was higher (11.4 ± 4.0 mg/dl vs. 12.9 ± 3.5 mg/dl, p < 0.001) and occurred later [74 (67-92) hours vs. 84 (70-103) hours; p = 0.04]. There was no difference in the need for intravenous fluids (1.6% vs. 4.9%; not significant) and readmissions (1.6% vs. 3.5%; not significant).Conclusion: Infants with AB0 alloimmunization needed more often phototherapy and were admitted longer after implementation of DCC policy. Further studies are needed to see whether the benefit of DCC outweighs the increased morbidity, admission days, and related hospital costs.